A sustainable strategy for effective regulation of aerobic granulation: Augmentation of the signaling molecule content by cultivating AHL-producing strains. (1st February 2020) - Zhang, Bing; Li, Wei; Guo, Yuan; Zhang, Zhiqiang; Shi, Wenxin; Cui, Fuyi; Lens, Piet N.L.; Tay, Joo Hwa
Abstract: The positive roles of N -acyl homoserine lactone (AHL)-mediated quorum sensing (QS) in aerobic granular sludge (AGS) have been widely acknowledged. However, it is not feasible to manipulate granulation via direct addition of AHL chemicals or AHL-producing strains. Here, several strains with high AHL-producing capacity were successfully isolated from AGS. These QS strains were cultivated, mixed as a consortium, and then divided into two groups: AHLs supernatant and bacterial cells encapsulated in sodium alginate (CEBs). The potential of QS regulation, via doses of AHLs supernatant and CEBs, in accelerating granulation was evaluated. Results clearly indicated that short-term (days 21–70) addition of AHLs supernatant led to a rapid specific growth rate (0.08 d −1 ), compact structure without filamentous bacteria overgrowth, excellent settlement performance (SVI10 37.2 mL/g), and a high integrity coefficient (4.4%) of the granules. Sustainable release of AHLs (mainly C6 - and C8 -HSL) was induced by exogenous AHLs, possibly attributed to the enrichment of the genera Aeromonas and Pseudomonas . Further, tryptophan and aromatic protein substances were produced to maintain structural stability, suggesting that short-term QS regulation had long-term positive effects on the characteristics of AGS. By comparison, the addition of CEBs posed negligible or negative impact on the granulation, as evidenced by the rupture of smaller aggregates and poor characteristics of AGS. Overall, augmentation of the signaling content via addition of AHLs supernatant from QS strains is an economical and feasible regulation strategy to accelerate granulation and sustain long-term structural stability. Graphical abstract: Image 1 Highlights: AHL-producing strains were isolated from AGS and further used for QS regulation. QS regulation via addition of AHLs supernatant enhanced granulation and activity. Dose of AHLs supernatant induced sustainable release of endogenous AHLs in the SBR. Sustainable release of AHLs promoted protein synthesis and maintained the stability. Dose of CEBs posed negative impacts on the AGS due to its high mechanical strength.